The effect of a patellar brace on three-dimensional patellar kinematics in patients with lateral patellofemoral osteoarthritis - McWalter, Emily J. (2011)
OBJECTIVE: Patellar bracing is a mechanical treatment strategy for patellofemoral osteoarthritis (OA) that aims to unload the lateral compartment of the joint by translating the patella medially. Our objective was to determine whether a patellar brace can correct patellar kinematics in patients with patellofemoral OA. DESIGN: We assessed the effect of a patellar brace on three-dimensional patellar kinematics (flexion, spin and tilt; proximal, lateral and anterior translation) at sequential, static knee postures, using a validated MRI-based method, in 19 patients with radiographic lateral patellofemoral OA. Differences in kinematics between un-braced and braced conditions were assessed in the unloaded and loaded knee (15% bodyweight load) using hierarchical linear random-effects models. Random slope and quadratic terms were included in the model when significant (p<0.05). RESULTS: Bracing with load caused the patellae to translate 0.46 mm medially (p<0.001), tilt 1.17° medially (p<0.001), spin 0.62° externally (p=0.012) and translate 1.09 mm distally (p<0.001) and 0.47 mm anteriorly (p<0.001) over the range of knee flexion angles studied. Bracing also caused the patellae to extend in early angles of knee flexion (p<0.001). The brace caused similar trends for the unloaded condition, though magnitudes of the changes varied. CONCLUSION: Bracing changed patellar kinematics, but these changes did not appear large enough to be clinically meaningful because no reduction in pain was observed in the parent study.